Facile Synthesis and Antimicrobial Evaluation of Some New Heterocyclic Compounds Incorporating a Biologically Active Sulfamoyl Moiety - Elham S. Darwish (The Scientific World Journal)
A facile and convenient synthesis of new heterocyclic compounds containing a sulfamoyl moiety suitable for use as antimicrobial agents was reported. The precursor 3-oxo-3-phenyl-N-(4-sulfamoylphenyl)propionamide was coupled smoothly with arenediazonium salt producing hydrazones which reacted with malononitrile or triethylorthoformate affording pyridazine and triazine derivatives, respectively. Also, the reactivity of the same precursor with DMF-DMA was followed by aminotriazole; aromatic aldehydes was followed by hydrazine hydrate, triethylorthoformate, or thiourea affording triazolo[1,5-a]pyrimidine, pyrazole, acrylamide, and dihydropyrimidine derivatives, respectively. On the other hand, treatment of the precursor propionamide with phenyl isothiocyanate and KOH in DMF afforded the intermediate salt which was treated with dilute HCl followed by 2-bromo-1-phenylethanone affording carboxamide derivative. While the same intermediate salt reacted in situ with chloroacetone, ethyl 2-chloroacetate, 3-(2-bromoacetyl)-2H-chromen-2-one, methyl iodide, or 2-oxo-N-phenylpropane hydrazonoyl chloride afforded the thiophene, ketene N,S-acetal, and thiadiazole derivatives, respectively. The structure of the new products was established based on elemental and spectral analysis. Antimicrobial evaluation of some selected examples from the synthesized products was carried out whereby four compounds were found to have moderate activities and one compound showed the highest activity.